Association of Neovascular Glaucoma with Risk of Stroke: A Population-Based Cohort Study - Cheng-Wen Su; Yue-Cune Chang; Cheng-Li Lin; Hsin-Yi Chen (Journal of Ophthalmology)
Neovascular glaucoma (NVG), caused by ocular ischemia, is a serious ocular disease complicated by intractably increased intraocular pressure. Cerebrovascular accidents are classified into ischemic and hemorrhagic stroke. Based on the similar pathogenic mechanisms of NVG and ischemic stroke, we investigated the relationship between NVG and stroke by using a nationally representative sample. This study included 416 NVG patients and 4160 controls. Medical comorbidities were also evaluated. The cumulative incidence of ischemic stroke was 15.6% higher in the NVG cohort than in the control cohort (p<0.001); the incidence density rates of stroke were 3.80 and 1.19 per 10,000 person-years in the NVG and control cohorts, respectively. According to the multivariable Cox regression results, the estimated adjusted hazard ratio (aHR) of stroke was 2.07 (95% confidence interval (CI) = 1.41–3.02) for the NVG cohort. Furthermore, the NVG cohort was 2.24-fold more likely to develop ischemic stroke (95% CI = 1.51–3.32). The risk of ischemic stroke was higher in patients with hypertension (aHR = 2.09, 95% CI = 1.55–2.82) and in patients with diabetic retinopathy (aHR = 1.69, 95% CI = 1.05–2.72). Notably, patients with NVG have a higher risk of ischemic stroke, but not hemorrhagic stroke.